Financial Inclusion for Financial Well-Being: Evidence from Pokhara, Nepal - Budhathoki, Dipika Sunar; Dhungana, Bharat Ram; Pokhrel, Om Prakash; Subedi, Chet Narayan; Acharya, Tara Nath (Journal of Development and Social Engineering, 2025)
Financial inclusion has become a significant issue in developing nations. Financial access is essential for the economic empowerment of the youth. This study uses a quantitative, primarily cross-sectional research design to examine the effect of financial inclusion on the financial well-being of youth in Pokhara Metropolitan City, Nepal. A convenience sampling technique was used, and a primary survey was conducted among 204 youths aged 18-29 years. Descriptive methods, correlation, and regression analysis were applied to examine the data. This study finds that youth financial well-being is primarily affected by affordability and usage of financial services. Providing financial services alone is not enough to promote people’s financial well-being; affordability and the use of financial services are equally important. Delivering affordable financial services, promoting active usage, and offering financial education and access ensure the financial well-being of youth. The outcomes of this research have significant policy implications for expanding affordable and productive usage of financial services. Policymakers may develop a strategy to ensure the productive application of affordable financial services to the welfare of youth and promote financial well-being.